Influence of Cognitive Bias on Decision Making in Mega Projects - ALNUAIMI, WALEED (2020)
Mega projects is an important topic in social sciences as it showcases the achievements attained by a group of people in a bid to advance the trend in a society through critical official transformation. Over the years, scholars, specialists, legislators, and the public have developed profound concern regarding mega projects exploring its characteristics and most importantly the consequences of these projects. In spite of mega projects yielding amazing outcome and benefits in the respective environments where they are executed, majority of research shows that the performance of projects is extremely below par especially in relation to expenses and time overruns which have been attributed to the features of mega projects which include complexity, wide scope, extended duration, huge funds and environmental settings that prompts increased risks to mega projects than other projects consequently increasing the rate of cost overruns. The main reasons for cost overrun have been clustered into three groups namely technical, optimism bias and strategic misrepresentation. Since mega projects are increasing in size and number, and their poor performance has been consistent despite various proposals suggested based on project management best practices that have mainly focused on the technical element of implementing mega projects, the performance in mega projects has not improved prompting this study to focus on optimism bias and strategic misrepresentation where if optimism is exceeded, it is termed as over optimism and leads to cost overrun due to significant underestimation of costs. The study builds on the view that cognitive biases have an influence of on cost overrun either directly or indirectly through decision making. Cost overruns are mainly influenced by decisions relating to costs and those that relate to risk. The study checked the influence of 12 cognitive biases that are controllability, availability, anchoring, conformation, cognitive dissonance, dread, familiarity, hindsight, scale, representativeness, optimism and venturesomeness on decision making (cost and risk) and cost overrun due to over optimism by developing a predetermined questionnaire using these factors and distributing it to decision makers in projects. Additionally, the influence of demographic attributes on cost overrun was also checked. 101 responses were received and analyzed through variance analysis, correlation, association analysis, and hierarchical regression. The association analysis which generated the key findings of the study indicated that work experience, controllability, dread, and cost decision making have significant influence on cost overrun due to over optimism while other factors were not significant. On the other hand, availability, anchoring, dread, and familiarity were found to significantly influence cost decision making, the other biases had no significant influence on cost decision making implying these biases have an influence on cost overrun through decision making. The hierarchical regression showed only work experience had an effect on both cost decision making and cost overrun while all other cognitive biases showed no impact indicating the presence of all biases at the same time does not have an influence on cost overrun but when considered individually which reflects high degree of the bias, controllability and dread biases have a direct influence on cost overrun due to over optimism whereas availability, anchoring, dread, and familiarity biases influence cost overrun through cost decision making in mega projects. The study proposes monitoring of all cost decisions in relation to these biases to ensure the biases do not impact on the project’s costs and hence do not influence cost overruns.